Longevity and subject‐reported satisfaction after minimally invasive jawline contouring. (18th September 2021) - Müller, Daniel; Prinz, Valentina; Sulovsky, Monika; Cajkovsky, Mia; Moellhoff, Nicholas; Cotofana, Sebastian; Frank, Konstantin
Abstract: Background: Minimally invasive treatments as soft tissue filler injections can enhance the appearance of the jawline. This prospective, single‐center study investigated aesthetic outcome, patient satisfaction, adverse events, and volume changes after jawline contouring using standardized reporting scales and objectifiable 3D surface analysis. Methods: A total of 30 patients (1 male and 29 females, mean age: 57.2 (±8.7) years) were investigated. Patients underwent jawline augmentation using a highly cross‐linked hyaluronic acid–based soft tissue filler. Three‐dimensional surface imaging was performed after 2 weeks, and 3, 6, 9, and 12 months. Furthermore, the aesthetic results and the occurrence of complications were investigated after two weeks, and 3, 6, 9, and 12 months. Results: The surface‐volume coefficient (SVC) had an average of 1.10 ± 0.2 after 14 days, 0.95 ± 0.1 after 3 months, 0.83 ± 0.1 after 6 months, 0.74 ± 0.1 after 9 months, and 0.63 ± 0.1 after 12 months. A significant correlation was revealed between time of measurement and measured SVC with rp  = −0.761, p  < 0.001. Multivariate analysis revealed a significant difference between the measured SVC and the different time points of measurement with p  < 0.001. The data revealed strong aesthetic improvement with results most often reported as "very much improved" according to the 5‐point GAIS after 3, 6, and 9 months, both by the investigator and by the patients. A 12‐month follow‐up analysis showed "much improved" results in a majority of cases. Conclusion: The result of this investigation showed that jawline enhancement using minimally invasive soft tissue filler injections produces durable, safe results that are generally rated as very satisfying from a patient's and investigator's perspective over a time period of 12 months.